Findings and outcome of revision lumbar disc surgery - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 1999)
One hundred fourteen patients (64 men, 50 women) with prior lumbar disc surgery underwent a reexploration for intractable back and/or leg pain. The finding in revision surgery included disc herniation in 89 cases (78%), epidural fibrosis in 14 cases (12.2%), adhesive arachnoiditis in 4 cases (3.5%), isolated lateral spinal stenosis in 3 cases (2.6%), and iatrogenic instability in 4 cases (3.5%). Review of operative reports of patients who underwent a first operation tin our institute revealed that seven cases (12.5%) had a second laminotomy without a discectomy in addition to the previous laminotomy and discectomy performed in the same session. Fifty-six of the patients with disc herniation in revision surgery had a true recurrence. Disc hemiation was protruded in 38 cases (42.8%), extruded in 44 cases (49.4%), and sequestrated in 7 cases (7.8%). The outcome was assessed using Prolo's functional and economic scale. According to Prolo's scale, a good outcome was detected in 79 cases (69.2%), moderate in 22 (19.2%), and a poor outcome was detected in 13 cases (11.4%). The best outcome was achieved in patients with disc hemiation. It is concluded that recurrent disc disease is the most important cause of reexploration. This fact dictates a careful preoperative workup and discectomy in the first intervention. The Likelihood of occurrence of disc herniation in the negative laminotomy level (i.e., laminotomy without discectomy procedure) also requires a careful preoperative radiologic workup before lumbar disc surgery.
Keywords: lumbar disc disease; reexploration; outcome; REOPERATION; SPINE; DISCECTOMY; HERNIATION; DISKECTOMY